2016
DOI: 10.1111/nph.14143
|View full text |Cite
|
Sign up to set email alerts
|

How do plants read their own shapes?

Abstract: Although the sensing of shape and deformation was historically involved in the control of animal locomotion, it is now increasingly being incorporated in developmental biology. Proprioception, the perception of the self, is particularly key to the question of the reproducibility of shapes: the many regulators of growth may lead to a large array of geometries, but shape sensing restricts these diverse outputs to a limited number of forms. Mechanistically, and in addition to geometrical feedback onto the diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 48 publications
1
61
0
2
Order By: Relevance
“…However, it has been found that a so called restoring force is required for stable posture control, termed proprioception (Bastien et al, 2013; Hamant and Moulia, 2016). This is related to an internal process associated with the active tendency of a growing organ to resist being bent (not a mechanical response), and is represented by , where γ is the proprioceptive sensitivity (Bastien et al, 2013).…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been found that a so called restoring force is required for stable posture control, termed proprioception (Bastien et al, 2013; Hamant and Moulia, 2016). This is related to an internal process associated with the active tendency of a growing organ to resist being bent (not a mechanical response), and is represented by , where γ is the proprioceptive sensitivity (Bastien et al, 2013).…”
Section: Governing Equationsmentioning
confidence: 99%
“…Recently developed models of growth-driven plant dynamics are limited to specific aspects of tropisms or circumnutations. Bastien et al have developed models for tropism in 2D, such as the AC (Bastien et al, 2013, 2015) and ACE (Bastien et al, 2014) models, addressing the influence of growth, and identifying the requirement of a restoring force called proprioception, whereby a plant can dampen the curving dynamics according to how curved it is (Bastien et al, 2013; Hamant and Moulia, 2016). Bressan et al (2017) developed a model based on a similar formalism however not accounting for growth explicitly as the driver of dynamics, and achieving stable dynamics by controlling the growth-zone and sensitivity, rather than proprioception.…”
Section: Introductionmentioning
confidence: 99%
“…The time scale of the problem is associated with the time it takes for the organ to reach its steady state, termed the convergence time and defined as T c = 1/γ. The ratio between the convergence length and the length of the organ introduces a dimensionless number Z [53], which describes the balance between the sensitivity to external stimuli and proprioception, and is linearly related to the maximal curvature:…”
Section: A Minimal Model For Allotropism: the Growth-driven Reorimentioning
confidence: 99%
“…Therefore, sensing these mechanical constraints through local tissue deformations, and consequently modulating growth to adjust the stem stability, represents an important developmental feedback to provide plants with postural perception. This is part of mechanism known as "proprioception" (1,4). The apical growth of trees is controlled by the cell division rate in the shoot apical meristem (SAM) that produces axillary primordia (later named stem nodes), combined with the longitudinal extension of shoot internodes.…”
Section: Introductionmentioning
confidence: 99%